Turning Waste into Taste: Effective Upcycling of By-Products for Innovative Food Solutions§ - Swapna Sree Meduri; Sujatha Mudawath; Prabhakar Butti; Soujanya Kanneboina; Sucharita Devi Tattepalli; Supraja Thoomati; Neela Rani Rathod; Aparna Kuna; Krishna Lavuri; Srinivasa Chary Darshanoju; Kanmani Kalaivanan (Food Technology and Biotechnology, 2025)
Waste management in the food manufacturing sector has become one of the most challenging aspects globally owing to the generation of enormous quantities of by-products, such as peels, seeds and undesirable flesh at various stages of the processing chain. However, these plant by-products are rich in important compounds particularly polyphenols and bioactive substances that significantly affect human health and can be utilised in numerous sectors as new, low-cost and economical raw ingredients. The aim of this review paper is to discuss various methods of valorising food waste, concentrating on upcycling, aquafaba, coffee silver skin, propolis, wine lees and avocado waste. Food waste is a substantial global issue, with the potential to affect food security, environment and economy. Upcycling is highlighted as a means to tackle food waste by repurposing high-value by-products such as fruit and vegetable residues. Aquafaba, a vegan alternative to egg white, is produced from chickpeas and has various culinary applications. Coffee silver skin, a by-product of coffee production, contains bioactive compounds that can be extracted and used in functional foods. Propolis, a resinous substance collected by bees, is rich in bioactive compounds with health benefits. Wine lees, a by-product of winemaking, can be processed to extract phenolic compounds and produce value-added products. Avocado waste valorisation focuses on converting avocado by-products into valuable products for various industries. The sustainable valorisation of food waste offers numerous benefits, such as reducing waste output, generating revenue and promoting resource efficiency. Collaboration between stakeholders is essential to advance research and implement sustainable management practices for food waste valorisation to achieve the Sustainable Development Goals (SDGs). Challenges such as scaling-up, regulatory frameworks, logistics, food safety and environmental impact must be addressed to effectively valorise food waste.